Are acinic cell carcinomas of the breast and salivary glands distinct diseases?. Issue 4 (23rd March 2015) - Piscuoglio, Salvatore; Hodi, Zsolt; Katabi, Nora; Guerini‐Rocco, Elena; Macedo, Gabriel S; Ng, Charlotte K Y; Edelweiss, Marcia; De Mattos‐Arruda, Leticia; Wen, Hannah Y; Rakha, Emad A; Ellis, Ian O; Rubin, Brian P; et al.
Abstract : Aims: Acinic cell carcinomas (AcCC) of the breast have been reported to constitute the breast counterpart of salivary gland AcCCs, based on the similarities of their histological and immunohistochemical features. Breast AcCC is a vanishingly rare form of triple‐negative breast cancer (TNBC). Recent studies have demonstrated that in TNBCs, the two driver genes most frequently mutated are TP53 (82%) and PIK3CA (10%). We sought to define whether breast AcCCs would harbour TP53 and PIK3CA somatic mutations, and if so, whether these would be present in salivary gland AcCCs. Methods and results: Sanger sequencing of the entire coding region of TP53 and of PIK3CA hotspot mutation sites of 10 breast and 20 salivary gland microdissected AcCCs revealed eight TP53 (80%) and one PIK3CA (10%) somatic mutations in breast AcCCs. No somatic mutations affecting these genes were found in the 20 salivary gland AcCCs analysed. Conclusions: Our findings demonstrate that breast AcCCs display TP53 and PIK3CA mutations at frequencies similar to those of common types of TNBCs, whereas these genes appear not to be altered in salivary gland AcCCs, suggesting that despite their similar histological appearances, AcCCs of the breast and salivary glands probably constitute unrelated diseases.